2020
DOI: 10.1080/1331677x.2020.1804427
|View full text |Cite
|
Sign up to set email alerts
|

The missing link between wages and labour productivity in tourism: evidence from Croatia and Slovenia

Abstract: The present article aims to analyse wage-labour productivity causalities in Croatia and Slovenia using cointegration methods based on monthly time series data of variables for labour productivity and real gross wages in tourism industry during the period December 1999-January 2020. The data vector is integrated by chain indices with the constant base January 2000 ¼ 100. A stochastic trend and shocks are covered in the analysis. Shocks are linked to the European Union accession, and economic crisis following wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…In a recent study, cointegration methodologies have been applied to the research of relationships between tourist arrivals and economic growth. In the article, as first descriptive statistics, second Granger representation theorem (Gri car et al, 2020;Johansen & Tabor, 2017):…”
Section: Methods Implementedmentioning
confidence: 99%
“…In a recent study, cointegration methodologies have been applied to the research of relationships between tourist arrivals and economic growth. In the article, as first descriptive statistics, second Granger representation theorem (Gri car et al, 2020;Johansen & Tabor, 2017):…”
Section: Methods Implementedmentioning
confidence: 99%
“…The issues of the dependence between labor productivity and wages do not lose their relevance as well. The considerable attention of the world academic community paid to this area fully confirms this statement (Gardiner et al, 2020;Gricar et al, 2020;Kong et al, 2020). Thus, Gardiner et al (2020) have investigated regional differences in labor productivity and found that they depend greatly on employees' wages.…”
Section: Introductionmentioning
confidence: 81%
“…Thus, Gardiner et al (2020) have investigated regional differences in labor productivity and found that they depend greatly on employees' wages. Gricar et al (2020) have analyzed the causal relationship between wages and labor productivity. Their results for the tourism industry show that labor force efficiency must increase in line with the rise in real wages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the 17 Sustainable Development Goals (SDGs) were adopted by the United Nations in 2015 as a universal call to action to end poverty, protect the planet and ensure that by 2030 all people enjoy peace and prosperity [34]. Some forms of tourism associated with the SDGs, such as low-carbon tourism [34][35][36], nomadic tourism [37][38][39], individual tourism with discrete individual tourist systems [40] and sustainable tourism [41,42], are used as independent variables in this study, while tourist arrivals are the dependent variable [43]. In analysing Croatian and Slovenian [43] tourism further development in the long run [44][45][46], the imperishable employees, as well as the tourism science competencies and the everlasting tourist should be considered as key elements where a shock [47] or an interruption of rain [48] or a crisis [49] should not be crucial development issues.…”
Section: Introductionmentioning
confidence: 99%